Isolation and Enrichment of Plant Growth Promoting Actinobacteria in Cow Dung Manure for Sustainable Biofertilizer Application - Alhaji Jinjiri, Babangida; Mahmud, Musa Muhammad; Mohammed Idriss, Maina; Ali, Lawan Gana; Mustapha, Umar Ali (PSM Microbiology, 2025)
The isolation and enrichment of plant growth-promoting Actinobacteria in cow dung manure were examined to improve its application as a biofertilizer. The sample is collected from the animal slaughterhouse (abattoir) in Geidam, Yobe State, Nigeria, dried in an oven at 45 °C for 24 hours, and homogenized for analysis of microbes. Dilution series were initiated from 10-1 to 10??, and species of Actinobacteria were cultivated on Starch Casein Agar (SCA) as selective media supplemented with ampicillin and nystatin. After primary cultivation, actinobacterial colonies were further enhanced by inoculating them in tryptic soy broth (TSB) and subsequently enriching them in dried cow dung manure at a moisture content of 50-60%, based on cell density (10?? CFU/g). Enriched cow dung is kept at mesophilic temperature for the growth of bacteria, additionally by a secondary mode of isolation as well as colony counting. The outcomes reveal a notable growth of Actinobacterial colonies, with CFU counts increasing from 3.9 × 10?? CFU/g prior to enrichment to 8.5 × 10?? CFU/g after completing the enrichment. Colony quantification verified the success of the enhancement, with fine, applicable and distinct actinobacterial strains viewed as well as the absence of contamination from the other bacteria. This investigation recommended that Actinobacteria enrichment can enhance the bio-fertilizer capacity of cow dung manure through boosting valuable strains of Actinobacterial species, resulting in soil well-being and eco-friendly agriculture production. Advanced investigation should place emphasis on land applications to confirm the prolonged effectiveness of enhanced cow dung manure as a biofertilizer or organic fertilizer.